Allelic losses and gains during translocations of a high conservation value fish, Coregonus lavaretus. Issue 9 (9th June 2021) - Præbel, Kim; Bean, Colin W.; Dodd, Jennifer A.; Etheridge, Elizabeth C.; Gowans, Andrew R.D.; Knudsen, Rune; Lyle, Alexander A.; Maitland, Peter S.; Winfield, Ian J.; Adams, Colin E.
Abstract: The use of translocations to establish new or 'refuge' populations for species with high conservation value is controversial but widely used in conservation management. One of the risks of this approach is that an establishing population does not adequately capture the genetic diversity of the donor gene pool. This effect, rarely examined, is tested here. In this study the genetic consequences of two conservation translocations after five generations (16 years) of the European whitefish, Coregonus lavaretus, were quantified. Both translocations were made using almost the same genetic groups and thus represent a partly replicated natural study. Analysis of 12 informative microsatellites showed that expected heterozygosity, the mean number of alleles per locus and allelic richness did not differ between donor and translocated populations. There was also no loss of heterozygosity in the translocated populations, nor deviations from Hardy–Weinberg equilibrium expectations, nor signs of linkage disequilibrium. All populations were genetically differentiated but pairwise F ST values were low, indicating that the magnitude of divergence was small. There was no evidence of inbreeding but there were significant differences in private allelic richness between donor and translocated populations. Of 50 alleles found in the donor population, 16% of the rarer alleles were lost in one translocated population and 8% in the other. Allele loss without a reduction in heterozygosity strongly points to stochastic drift effects having occurred following translocation. The evidence indicates that alleles that were not detected in the donor population have arisen de novo in the translocated populations. It is concluded that conservation translocations comprising even a modest number of propagules can successfully capture a high proportion of genetic variation of the host population, and that reduced genetic variation in the translocated population may be mitigated by the emergence of new variation over short time periods.